Professional learning and skills development in the European Film industry: interest, capacity, learning modes, and future priorities - Granström, Mikk; Liiske, Marge; Tramberg, Triin; Lokk, Tiina (Frontiers in Communication, 2026)
This study examines how professionals in the European audiovisual sector engage with skills development and how they perceive different modes of professional learning. Data were collected from 355 professionals across diverse roles, career stages, and countries. Quantitative and qualitative analyses addressed five research questions: (1) interest and capacity for training, (2) preferred learning modes, (3) future skill priorities, (4) financial security and access to support, and (5) evaluations of training opportunities in Europe. The findings indicate that while online courses are widely used, participants often view them as complementary to in-person formats, particularly for practice-oriented or collaborative learning. Respondents also frequently emphasized the value of networking and peer exchange within professional learning environments, though not at the expense of skill development. The study contributes to research on skills ecosystems in the creative industries by offering empirically grounded insights into how workers navigate fragmented training landscapes and by outlining implications for designing more coherent and accessible upskilling pathways across Europe.